Lumbar Spinal Cord Activity and Blood Biochemical Changes in Individuals With Diabetic Peripheral Neuropathy During Electrical Stimulation - Jia, Yanlong; Shen, Zhiwei; Lin, Guisen; Nie, Tingting; Zhang, Tao; Wu, Renhua (Frontiers in Neurology, 2019)
It is difficult to perform an in vivo evaluation of the nerve conduction mechanism in a patient with diabetic peripheral neuropathy (DPN). We aim to explore possible activation differences to enable further understandings of the nerve conduction mechanisms of diabetic neuropathy and to present a novel clinical method to objectively evaluate nerve injury and recovery. DPN patients (n = 20) and healthy volunteers (n = 20) were included in this study to detect the functional activation of the lumbar spinal cord via electric stimulation. Spinal fMRI data sets were acquired via a single-shot fast spin echo (SSFSE) sequence. A task-related fMRI was performed via low-frequency electrical stimulation. After post-processing, the active voxels and the percentage of signal changes were calculated for the DPN evaluation and the correlations between the blood biochemical indexes, such as glucose, total cholesterol, and hemoglobin A1c were explored. Activation in the DPN patients was primarily observed in the T12 (10/13) vertebral level. The percentage of signal changes in DPN patients was higher than that in the control group (Z = - 2.757, P < 0.05). Positive correlation between the percentage of signal changes and the total cholesterol/glucose in the DNP group was found (P < 0.05). Lumbar spinal cord fMRI, based on the SEEP effect, was determined to be feasible. The repetitive activation distribution was primarily located at the T12 vertebral level. Lumbar spinal cord fMRI is a very useful tool to objectively assess and reveal the nerve conduction mechanisms in DPN.